TRAINING TEACHERS FOR ORGANIZING CONDITIONS FOR SOCIALIZATION OF CHILDREN IN DIFFICULT LIFE SITUATIONS - Stukalova, Olga; Skvortsova, Tatyana (Revista Inclusiones, 2020)
The relevance of the present study is determined by the need to train modern teachers called upon to solve multifaceted tasks in the field of pedagogical support for children in difficult life situations, including the process of their socialization. The aggravated social cataclysms are clearly interconnected with the problems of socialization, constructive relationships between a person and society, and the possibility of completed self-actualization. The article is aimed at developing a strategy for training pedagogical university students that would provide the ability to master modern technologies and methods of relying on the potential of art that allow children to develop the necessary skills, productive coping strategies, and internal locus of control and learn how to overcome emotional burnout and various manifestations of deviations and be emotionally stable. The authors develop content and structure of a training course entitled “Pedagogical support for children in difficult life situations: socialization via the means of art”. The diagnostic instruments are developed. The article examines the main conditions for effective approbation of the course and directions for assessing its impact on improving students’ professional competence in the field of socialization of children in difficult life situations. The article also presents the results of experimental work on course introduction and approbation at the Moscow State Pedagogical University and the Tver State University. The article is targeted for researchers, teachers, and methodologists dealing with the issues of social pedagogy.